Model of Use Management Tools (Journal of Universal Excellence, 2026)
Research Question (RQ): What is the impact of management tools on the economic performance of a company's business (return on capital)?Purpose: To create a SEM model of the influence of the use of manager tools on the economic performance of the company.Method: A quantitative survey in which we obtain data and information obtained through the questionnaire and search the public database of GVin.Results: Using the results of quantitative research we developed a conceptual model of the impact of the use of manager's tools on economic performance.Organization: Based on the study of contemporary literature, comparisons of different has already carried out research and surveys of executive managers in large and medium-sized Slovenian companies, we formed the original model of the use of selected managerial tools on the profitability of capital companies.Society: The survey highlights managers' focus on solving operational problems and much less emphasizes their vision and leadership skills.Originality: Based on the obtained data, we acquired a new comprehensive view, knowledge and information on the use of selected manager tools and their impact on profitability.Limitations / further research: The survey will be carried out in large and medium-sized enterprises in Slovenia, we will discuss selected 25 management tools for Rigby-ROM, we will use data from publicly available databases.
Keywords: management; manager's tools and techniques; Slovenian companies; model; Return On Equity; economics